Percepção de fala em crianças escolares do 3º ao 5º ano do Ensino Fundamental: proposta de avaliação - Appezzato, Mariana Martins [UNIFESP] (2017)
To elaborate an protocol for assessment of speech perception, investigate its internal consistency, describe speech perception and phonological representation skills in typical school children, and investigate the presence of correlations between the studied variables. Method: Sixty typical children (60% female), regularly enrolled in the 3rd, (N=14), 4th (N=24) and 5th (N=22) grade of the Elementary School, with ages ranging between 08 years, 02 months to 11 years, 08 months old (99 to 136 months; M=120,05; DP = 10,26) were evaluated. A protocol included 06 tasks to assess reception skills of speech stimulus: (A) speech perception of verbal and non-verbal sounds; (B) discrimination of non-words with the structure of the Portuguese Language; (C) discrimination between the syllabic structure of the Portuguese Language and of the syllabic structure of another language; (D) perception of phonetic features that distinguishes words in Portuguese; (E) correlation between image and the pronunciation of the word in Portuguese; (F) reception of alliteration and rhymes; and (G) feedback. The evaluations occurred within the period comprised of the end of the 1st school semester and the beginning of the 2nd school semester of 2016. The data were analysed by Cronbach’s Alpha Coefficient, Spearman and Pearson’s Correlation Coefficient with significance level of 0,05. Results: The items of tasks (B) and (C) showed good internal consistency (α=0,84; α =0,80); the items of task (C) in the answers Portuguese/Non-Portuguese showed acceptable internal consistency (α=0,76). The other tasks showed poor and unacceptable consistency. It was observed the effect of the school year in the answers of children only in tasks (C), in the Portuguese/Non-Portuguese answers, in the equal/different (E/D) and in task (D). Conclusion: Considerable part of the proposed items to the speech perception evaluation showed internal consistency. The task of discrimination of non-words with the structure of the Portuguese Language and the task of discrimination between the syllabus structure of Portuguese Language and another language showed reliable to evaluate typical children’s skills. On the other hand, for other tasks it will be necessary some substitutions of excluded items, in order to adequate the protocol’s reliability. The older the children, or the more advanced the school grade, the better the auditory perception capacity and discrimination capacity for syllabic structure. Some items from the questionnaire predicted auditory perception skills and discrimination capacity for Portuguese syllabic structure.